DapF stabilizes the substrate-favoring conformation of RppH to stimulate its RNA-pyrophosphohydrolase activity in Escherichia coli. Issue 13 (21st June 2018) - Wang, Qiang; Zhang, Delin; Guan, Zeyuan; Li, Dongqin; Pei, Kai; Liu, Jian; Zou, Tingting; Yin, Ping
Abstract: mRNA decay is an important strategy by which bacteria can rapidly adapt to their ever-changing surroundings. The 5′-terminus state of mRNA determines the velocity of decay of many types of RNA. In Escherichia coli, RNA pyrophosphohydrolase (RppH) is responsible for the removal of the 5′-terminal triphosphate from hundreds of mRNAs and triggers its rapid degradation by ribonucleases. A diaminopimelate epimerase, DapF, can directly interact with RppH and stimulate its hydrolysis activity in vivo and in vitro . However, the molecular mechanism remains to be elucidated. Here, we determined the complex structure of DapF–RppH as a heterotetramer in a 2:2 molar ratio. DapF-bound RppH exhibits an RNA-favorable conformation similar to the RNA-bound state, suggesting that association with DapF promotes and stabilizes RppH in a conformation that facilitates substrate RNA binding and thus stimulates the activity of RppH. To our knowledge, this is the first published structure of an RNA–pyrophosphohydrolysis complex in bacteria. Our study provides a framework for further investigation of the potential regulators involved in the RNA–pyrophosphohydrolysis process in prokaryotes.